(3GdQLGds - (3GdMSf Hf Ydj Hf OGhO, Jbqj GdOjf, GdeYQha HGHf OGhO GdMdj,J (B740 (3g` s ((3TQja Hf HgGA GdOjf Hf Ydi GdSfj s)
(3ChdgG (B:s
(3CeG HYO MeO Gddg Ydi CaVGdg aEfj deG CfgjJ GdLRA GdChd ef cJGH GdQLGd GdeNJU HGdehKbjf, hYLH Ydi Cf CJHYg HGdLRA GdKGfj s
(3BNQgG (B:s
(3CHhjYbhH GdeYeQi RjOi s
(3hYdjg ebGHdI SfI (B969 (3g`s
(3bQf GdfSN (B:s
(3GdbQf GdYGTQs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B2 - (3U (B204 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B3 - (3U (B253s
(3HQhcdeGf edMb (B- (3GdLRA (B2 - (3U (B970 ; (3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA JGQjN (B- (3bSe (B4 - (3U (B189 s
Keywords: (3GdJGQjNs